Comparison of Facial Nerve Function Outcomes in the Surgical Treatment of Cerebellopontine Angle Lesions with or without Intraoperative Neurophysiological Monitoring - Küçükyürük, Barış; Taşkıran, Emine (Cerrahpaşa Medical Journal, 2021)
Objective: Intraoperative neurophysiological monitoring (IONM) is commonly used in preserving the function of the facial nerve (FN) during surgery for cerebellopontine angle (CPA) lesions. In this study, we aimed to compare the outcomes of FN function in patients who were treated for CPA lesions with or without IONM. Methods: This study included 37 patients (22 women, 15 men). The patients were divided in two groups based on whether IONM was used (group 1) or not (group 2). The FN function was graded according to House–Brackmann (HB) Score. HB scores of 1–3 and 4–6 were considered favorable and unfavorable outcomes, respectively. Demographic information, surgical resection rates, type of pathology, and FN function were evaluated retrospectively. Comparisons between groups were conducted using nonparametric tests. Results: The mean age of the patient group was 45.2±14.82 years and the range was 16–72 years. There were 17 patients in group 1 and 20 patients in group 2. At the 1-year examination, 6 patients (35.3%) in group 1 and 2 patients (10%) in group 2 had unfavorable FN function. A 1-year postoperative comparison of the groups, in terms of the presence of disfiguring FN palsy, showed a statistically significant difference (p=0.03). Conclusion: The use of IONM during surgery of CPA lesions promoted the preservation of FN function with a secondary benefit of facilitating maximal resection. Cite this article as: Küçükyürük B, Taşkıran E. Comparison of Facial Nerve Function Outcomes in the Surgical Treatment of Cerebellopontine Angle Lesions with or without Intraoperative Neurophysiological Monitoring. Cerrahpaşa Med J 2020; 45(1): 5-9.